Updated roles of cGAS-STING signaling in autoimmune diseases - Liu, Ya; Pu, Feifei (Frontiers in Immunology, 2023)
Natural immunity, the first line for the body to defense against the invasion of pathogen, serves as the body's perception of the presence of pathogens depends on nucleic acid recognition mechanisms. The cyclic GMP-AMP synthase-stimulator of the interferon gene (cGAS-STING) signaling pathway is considered an essential pattern recognition and effector pathway in the natural immune system and is mainly responsible for recognizing DNA molecules present in the cytoplasm and activating downstream signaling pathways to generate type I interferons and some other inflammatory factors. STING, a crucial junction protein in the innate immune system, exerts an essential role in host resistance to external pathogen invasion. Also, STING, with the same character of inflammatory molecules, is inseparable from the body's inflammatory response. In particular, when the expression of STING is upregulated or its related signaling pathways are overactivated, the body may develop serious infectious disorders due to the generation of excessive inflammatory responses, noninfectious diseases, and autoimmune diseases. In recent years, accumulating studies indicated that the abnormal activation of the natural immune cGAS-STING signaling pathway modulated by the nucleic acid receptor cGAS closely associated with the development and occurrence of autoimmune diseases (AID). Thereof, to explore an in-depth role of STING and its related signaling pathways in the diseases associated with inflammation may be helpful to provide new avenues for the treatment of these diseases in the clinic. This article reviews the activation process of the cGAS-STING signaling pathways and its related important roles, and therapeutic drugs in AID, aiming to improve our understanding of AID and achieve better diagnosis and treatment of AID.